Constructing and Standardizing Administrative Bureaus Transitional Leadership Scales in Olympic Central Federation from the General Bureau’s Point of View - Abbas, Hiba; Jalal, Ali (Journal of Physical Education, 2021)
The importance of the research lies in transitional leadership as a new topic in sport administration and especially in Iraqi national Olympic federations. The researchers constructed a scale for measuring transitional administration in Olympic federation members from administrative members’’ point of view. The scale consisted of (8) fields and was distributed on (73) items. The data was collected and treated using proper statistical operations to conclude that Olympic federations’ members have many standards levels while general bureau members gained an intermediate level in transitional leadership scale.